Identifying attributes of public transport services for urban tourists: A data-mining method. (May 2021) - Ram, Yael; Gal-Tzur, Ayelet; Rechavi, Amit
Abstract: The current work focuses on Quality of Service (QoS) of Public Transport (PT) attributes in urban tourist destinations. In particular, we aim to reveal which attributes are most significant for tourists prior to their arrival at their destination, as reflected in questions posted in TripAdvisor Question and Answer forums, a widely used social media platform. We used a data-mining method to classify questions into categories relevant to QoS, using a sample of 8905 items posted between 2005 and 2018 in TripAdvisor forums for seven urban destinations in the United States and Western Europe. We found four PT-QoS attributes: Pricing and ticketing, Accessibility, Trip duration, and Service availability (hours of operation and frequency). These attributes have similar relative significance for all destinations, origins, seasons, and years we checked. Hence, they can help service operators and policymakers to understand tourists' preferences and to adjust PT services accordingly. Highlights: We investigate tourists concerns with public transport Quality of Service (QoS). Questions from TripAdvisor Q&A forums of seven tourists' cities are analyzed. Four prominent QoS attributes are identified using a data-mining method. The QoS: Pricing and ticketing, Accessibility, Trip duration, Service availability The attributes are stable across years, destinations, tourists' origin, and seasons.